The memory of water: uses and customs of the askòs in Magna Graecia (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2024)
This paper presents the initial findings of a study on the askòi from centers in Magna Graecia belonging to the Ionian arc and from indigenous areas between the Ofanto and Basento rivers, beginning with those identified at Jazzo Fornasiello (Gravina in Puglia, BA). The objectives are twofold: to study the morphological evolution of the askòs, from the 9th to the 1st century B.C., and to identify the role and function of this vase type. The latter aspects can be inferred from various elements, including analyses of the study of the askòi’ conformation and dimensions and the substances stored in the containers (such as water, wine, vinegar and oil), the investigation of the contexts of their discovery and the examination of the different associations of materials identified in them. The proposed interpretation of the askòi is that they also served as containers for storing and transporting potable liquids, as suggested by both the current state of research and the iconographic repertoire
Keywords: askòi; water; wine; oil; storage; transportation